Diagnosis and Management of Chronic Appendicitis in Children: A Case Report - Mutiara Annisa Amadea; Yusri Dianne Jurnalis (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Abdominal pain was one of the most complaints in children. Chronic appendicitis was the common cause of recurrent abdominal pain. The incidence of this case was 1,5% of all appendicitis cases. The manifestation was not specific, and one of the treatment options was surgical with laparotomy or laparoscopy methods. Case presentation: A 10-year-old boy came to the outpatient clinic of gastroenterohepatology with a diagnosis of abdominal pain caused by chronic appendicitis differential diagnosis of chronic gastritis with abdominal pain, especially the pit of the stomach moving to the right waist since 3 months ago. Physical examination of the patient showed the general condition was moderate, conscious, and normal vital signs. Abdominal distension was absent, tenderness in the lower right abdomen was present, and the pain was present in the lower right abdomen. There was contralateral tenderness in the left lower abdomen. An appendicogram examination shows chronic appendicitis. The patient was consulted for pediatric surgery for appendectomy and later controlled to a surgical outpatient clinic after discharge. Conclusion: Chronic appendicitis usually shows unspecific manifestation and physical examination. Early diagnosis and surgical treatment are options to treat appendicitis in children.